Pain Relief by Analgesic Eardrops: Paradigm Shift in the Treatment of Acute Otitis Media? - Michel, Olaf (Drug Research, 2021)
Acute otitis media is a common middle ear infection in children with the predominant symptoms of hearing impairment and pain. If antibiotics are given, they need time to have an effect on the inflammation, so the focus is on pain control. For pain management local anesthetics have the advantage of lesser systemic side effects but are still subject to scrutiny. In this review the literature between 2000 and 2020 was systematically searched for investigating studies and recommendation in guidelines against the background of the mode of action. 11 clinical studies, 2 guidelines and 5 reports resp. reviews could be identified. Contraindications and side effects were not found in these studies. The analgesic ear drops showed in placebo-controlled studies a relatively short duration of action when applied once but rapid onset of action. There is evidence that analgesic ear drops could provide a first-line analgesia in otitis media without systemic adverse effects such as gastrointestinal disturbance and nausea and could support an antibiotic-saving wait-and-see attitude. The review shows a change in attitude towards the recommendation to include local anesthetics ear drops in otitis media but still there is a lack in treatment protocols which go beyond a single administration. The results do not yet show a significant paradigm shift. The reviews revealed indications that a more adapted galenic preparation could give more effectiveness. Pharmaceutical research in this field should be intensified to exploit the analgesic potential of local anesthetic ear drops in acute otitis media.
Keywords: Local anesthetic treatment; acute otitis media